Back to school during the COVID-19 pandemic: Mitigating risks while promoting individual and community well-being - Ngov, Cindy; Miconi, Diana; Papazian-Zohrabian, Garine; Rousseau, Cécile (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2021)
Unplanned school closures such as the ones brought on during the COVID-19 pandemic are a catalyst for many developmental consequences on the youth and their families. Although guidelines exist to mitigate viral transmission, school-based interventions that can help alleviate the other consequences of the current crisis have yet to be documented. For students, these include the exacerbation of mental health difficulties, widening educational and socioeconomic disparities, and intercommunity tensions. Literature on unplanned school closures can inform best practices for school re-entry. Acknowledging educational, societal, and mental health disparities is an essential part of supporting the transition. Psychological first aid interventions, capacity-building and a response-to-intervention approach can help mitigate the effects of the pandemic and are implementable even in low-resource classrooms.